Uterine Sensitization-Associated Gene-1 in the Progression of Kidney Diseases - Xiaohu Li; Wenlong Yue; Guiwen Feng; Jinfeng Li (Journal of Immunology Research)
Uterine sensitization-associated gene-1 (USAG-1), originally identified as a secretory protein preferentially expressed in the sensitized rat endometrium, has been determined to modulate bone morphogenetic protein (BMP) and Wnt expression to play important roles in kidney disease. USAG-1 affects the progression of acute and chronic kidney damage and the recovery of allograft kidney function by regulating the BMP and Wnt signaling pathways. Moreover, USAG-1 has been found to be involved in the process of T cell immune response, and its ability to inhibit germinal center activity and reduce humoral immunity is of great significance for the treatment of autoimmune nephropathy and antibody-mediated rejection (AMR) after renal transplantation. This article summarizes the many advances made regarding the roles of USAG-1 in the progression of kidney disease and outlines potential treatments.